PERKEMBANGAN PENDIDIKAN ISLAM DI CINA - St. Aisyah Abbas (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2021)
This article discusses the development of Islamic education in China using a historical approach. The results of the discussion obtained an understanding that the earliest Muslim communities in China were descended from traders, militias, and Muslim officials from Arab, Persian, Central Asian, and Mongolian origin who originally settled along the southeast coast of China in the 7th century AD although At first Muslims were considered foreigners, but because of their ability to communicate persuasively and assimilate with Chinese society, Islam was accepted by the Chinese peacefully and voluntarily, even some dynastic officials in China and other tribes embraced Islam. Then they built a mosque in every settlement of Chinese Muslims. Islamic education in China is developed through education in mosques, known as the